BACOPA MONNIERI DAN KESEHATAN NEUROLOGIS: TINJAUAN LITERATUR TERHADAP STUDI YANG MENELITI PERANNYA DALAM MENINGKATKAN FUNGSI KOGNITIF - Isnaniah, Isnaniah; Aprilea, Noor Adha; barkinah, Tut; Kirana, Rita (Bajang Institute, 2024)
Background: This literature review critically examines existing research on Bacopa monnieri, an herb renowned for its cognitive-enhancing properties. Objective: To investigate the impact of Bacopa monnieri on neurological health, with a particular focus on its role in improving cognitive function. Methods: A systematic literature search was conducted across major databases, including PubMed, Scopus, and Google Scholar, to identify relevant studies published to date. Inclusion criteria consisted of randomised controlled trials, observational studies, and systematic reviews exploring the cognitive effects of Bacopa monnieri on human subjects. Studies that examined different aspects of cognitive function, including attention, memory, and processing speed, were also included. Results: This review included a comprehensive analysis of 5 studies that met the inclusion criteria. The studies collectively revealed a spectrum of cognitive benefits associated with Bacopa monnieri supplementation. Significant improvements were observed in attention and memory-related tasks across different age groups. The neuroprotective, antioxidant and anti-inflammatory properties of Bacopa monnieri, attributed to active compounds such as bacosides, were often implicated in the observed cognitive improvements. Conclusion: Bacopa monnieri is emerging as a promising natural intervention for improving cognitive function, with a growing body of evidence supporting its neuroprotective effects. While methodological variations exist among studies, the overall trend suggests that Bacopa monnieri has the potential to address cognitive decline associated with ageing and other neurological conditions. This review provides a nuanced understanding of the current state of knowledge, emphasising the need for further well-designed trials to elucidate optimal dosage, duration, and potential long-term effects. The findings contribute to the ongoing discourse on natural interventions for cognitive enhancement and provide valuable insights for researchers and healthcare practitioners.